2000
DOI: 10.1103/physrevb.61.r5082
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of weak localization and a metallic phase in Si/SiGe quantum wells

Abstract: Magnetoresistivity measurements on p-type Si/SiGe quantum wells reveal the coexistence of a metallic behavior and weak localization. Deep in the metallic regime, pronounced weak localization reduces the metallic behavior around zero magnetic field without destroying it. In the insulating phase, a positive magnetoresistivity emerges close to B=0, possibly related to spin-orbit interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 57 publications
7
38
1
Order By: Relevance
“…But due to the lack of the "metallic" state in these low-mobility samples, no appropriate conclusion could be drawn. In recent studies on high-mobility samples with "metallic" behavior, it was shown that the WL has only small effects on ρ for GaAs/AlGaAs [6] and Si/SiGe [7]. Also for Si-MOS structures in the low ρ (high n) regime, the WL contribution is small and it was shown that spinorbit coupling is not visible for τ ϕ up to 100 ps [8].…”
mentioning
confidence: 99%
“…But due to the lack of the "metallic" state in these low-mobility samples, no appropriate conclusion could be drawn. In recent studies on high-mobility samples with "metallic" behavior, it was shown that the WL has only small effects on ρ for GaAs/AlGaAs [6] and Si/SiGe [7]. Also for Si-MOS structures in the low ρ (high n) regime, the WL contribution is small and it was shown that spinorbit coupling is not visible for τ ϕ up to 100 ps [8].…”
mentioning
confidence: 99%
“…(iii) Some experiments have been successfully interpreted in the framework of normal Fermi-liquid behavior of charge carriers on the metallic side of the transition (using the Hartree-Fock approximation), including weak-localization corrections [100,102,103]. In [102], magnetoresistance measurements were used to extract the logarithmic corrections to the Drude conductivity in the 'metallic' phase of a high-quality two-dimensional GaAs hole system at low temperatures.…”
Section: Evidence Against a True Metal-insulator Transition In Two-dimentioning
confidence: 99%
“…10,13 Both studies find values of three to five times smaller than those predicted from Fermi-liquid theory. Phase breaking rates −1 have also been extracted and compared to theoretical values in other material systems, for example, p-SiGe, 9,15 and Si. 12 In all these cases where the method of Hikami was used to fit the data, the value of extracted was found to differ by the factor of 3-5 from the theoretical value.…”
Section: B Analysis Of the Phase Breaking Rate In P-gaasmentioning
confidence: 99%
“…Analysis of this positive magnetoconductivity has been widely used to measure the phase-coherence time and probe the dephasing mechanisms in 2D systems. [5][6][7][8][9][10][11][12][13][14][15] In order to reliably extract from the measured data it is essential to have an accurate method for determining the effect of the weak localization on the magnetoconductivity. While a good physical understanding of the weak localization effect exists, the numerical process by which experimental data are analyzed is not so well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation